Quantum quenches in 1 + 1 dimensional conformal field theories. (24th June 2016) - Calabrese, Pasquale; Cardy, John
Abstract: We review the imaginary time path integral approach to the quench dynamics of conformal field theories. We show how this technique can be applied to the determination of the time dependence of correlation functions and entanglement entropy for both global and local quenches. We also briefly review other quench protocols. We carefully discuss the limits of applicability of these results to realistic models of condensed matter and cold atoms.